Free Riding and Collective Action: An Experiment in Public Microeconomics - Schneider, Friedrich; Pommerehne, Werner W. (Quarterly Journal of Economics, 1981)
The well-known free-rider hypothesis is examined experimentally to see (i) whether individuals behave systematically as free riders when systematic incentives to do so are created, and (ii) the extent to which free riding actually occurs. Though the experiment's participants behaved in accordance with the hypothesis, the quantitative extent to which such behavior occurred was rather modest. From this it may be concluded that the free-rider hypothesis as presently stated indicates an incompleteness in standard public microeconomics rather than providing a description of the real world.